ПАЙГАМБАРЛАР КАЛТЫРГАН БААЛУУЛУКТАР - Ахмедова, Замира (Scientific Journal of Faculty of Theology, 2015)
In this article, we gave examples from the life of the prophets. Emphasized the importance to Muslims. Especially Prophet Muhammad's morals are described. Because Allah has introduced him as a best model. Key Words: The life of the Prophets, Morals, Values, Exemplary